Assessment of failure pressure of a GFRP composite repair system for wall loss defect in metallic pipelines: Beurteilung des Druckabfalls von einem Glasfaser‐Verbundwerkstoff‐Reparatursystem bei Wanddickenverlust in metallischen Pipelines. Issue 7 (20th July 2018) - Budhe, S.; Banea, M.D.; de Barros, S.; Rohem, N.R.F.
Abstract: The present paper is concerned with the failure pressure assessment of a newly developed GFRP matrix laminated composite repair of metallic pipelines with 80 % wall loss defect. The main motivation is to validate the experimental failure pressure with the theoretical one. Wall loss defects were manufactured into the tube specimen and the performance of the repaired pipe was assessed by hydrostatic tests as per ISO/TS 24817 standard. Results reveal that the theoretical failure pressure as per ISO/TS 24817 standard is found to be conservative. A wide range of failure pressure values was obtained using different criteria. Only RSTRENG 0.85* modified criterion provides a closer value towards the experimental one. However, the criterion selection for damage factor and flow stress condition is an open question as it gives dispersed values of failure pressure. The prediction of the failure pressure must be accurate without being overly conservative. Plastic deformation of the tube occurs towards the end of the tube, consequently, it is necessary to account for this behavior in failure pressure analysis for an accurate prediction. The application of loading‐unloading cycles before the failure burst test should be also accounted in order to predict the failure pressure.